1978
DOI: 10.1002/pol.1978.180160112
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of isotactic poly(4‐methyl‐1‐pentene)

Abstract: The crystal structure of isotactic poly(4‐methyl‐1‐pentene) was determined by x‐ray analysis. The unit cell is tetragonal, P4b2, with α = 18.70 Å and c (fiber axis) = 13.68 Å; it contains four molecular chains each consisting of seven monomeric units in the fiber period. The molecular conformation is essentially a (7/2) helix, but deviates slightly from the uniform (7/2) helix. The unusual low density is discussed from the structural point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 22 publications
7
123
0
Order By: Relevance
“…This result suggests the width of the cavity in PMP crystal lies between 4.1 Å that is the diameter of CO 2 and CH 4 and 5.2 Å that is that of C 3 H 8 . This estimation is fundamentally consistent with the results obtained from X-Ray analysis by Kusanagi et al and gas transport measurements by Paul et al 8,10,11 Xe Sorption and 129 Xe NMR Measurements Figure 3 shows Xe sorption isotherms of PMP membranes at 25 • C. It appears that sorption amount of Xe increases in proportion to applied pressure. These isotherms can be described by the Henry's mode sorp- …”
Section: Xe Nmr Measurementssupporting
confidence: 81%
See 1 more Smart Citation
“…This result suggests the width of the cavity in PMP crystal lies between 4.1 Å that is the diameter of CO 2 and CH 4 and 5.2 Å that is that of C 3 H 8 . This estimation is fundamentally consistent with the results obtained from X-Ray analysis by Kusanagi et al and gas transport measurements by Paul et al 8,10,11 Xe Sorption and 129 Xe NMR Measurements Figure 3 shows Xe sorption isotherms of PMP membranes at 25 • C. It appears that sorption amount of Xe increases in proportion to applied pressure. These isotherms can be described by the Henry's mode sorp- …”
Section: Xe Nmr Measurementssupporting
confidence: 81%
“…It is one of the significant properties of PMP that the density of crystal region is lower than that of amorphous region. [5][6][7] Kusanagi et al have investigated the crystal structure of PMP 8 termed as "Form I", 9 which is characterized by molecular chains in 7/2 helical conformation packed in a tetragonal unit cell, and concluded that the lower density of crystal region is attributed to a coarse packing of the chains, as a result, the cylindrical cavity with a diameter of about 4 Å is formed in the crystal. This fact means that transport phenomena of gas and vapor molecules occur in not only amorphous but also crystal regions.…”
mentioning
confidence: 99%
“…32 Its crystal structure consists of four 7/2 helices packed in a tetragonal unit cell of dimensions a = 18.70 Å and c = 13.68 Å. This structure was investigated at atomic level by refining the X-ray data with a constrained least-squares (CLS) method.…”
Section: Nvt Simulations Of Crystalline Poly(4-methyl-1-pentene)mentioning
confidence: 99%
“…The starting geometry for the MCDP simulations was taken from Ref. 32. Accordingly, four helices were packed in a tetragonal box at the positions indicated in Figure 5.…”
Section: Nvt Simulations Of Crystalline Poly(4-methyl-1-pentene)mentioning
confidence: 99%
“…Daubeny, 0021-8898/87/030246-10501.50 © 1987 International Union of Crystallography Bunn & Brown, 1954;Holmes, Bunn & Smith, 1955) and was still being used a few years ago (e.g. Kusanagi, Takase, Chatani & Tadokoro, 1978). However, singlescan microdensitometers are now widely used, with arc-correction factors being applied for the azimuthal spread of reflections and its change with diffraction angle (e.g.…”
Section: Introductionmentioning
confidence: 99%